Smart White Board Eraser (SWBE) - H. Mohd Rizal; B.A. Mohamad Fadzil; M.Y. Jasni (Universiti Sains Islam Malaysia, 2024)
Lecturers in Politeknik Seberang Perai are responsible in the teaching and learning processes. Whiteboards are used by the lecturers to further explain the course content and facilitate sharing of individual thoughts in group discussions. Unfortunately, whiteboards are erased by manual user action, which are tedious. Sometimes, whiteboards are left unclean because lecturers from previous classes need to hurry to catch up with the next class. Typically, a user would obtain an eraser and then apply the eraser to the surface of the whiteboard in an often non-uniform motion to wipe-off the hand-written notations thereon. Such manual erasure is time consuming and deemed a chore which will indirectly affect the morale of the students. Although electronic whiteboards are available and gaining favor in the marketplace, they are more expensive. As a result, Smart White Board Eraser is designed to solve these problems. It composed of a main body, a power unit 12V dc motor, operatively connected to the support means to drive the eraser member across the board while the support means supports the eraser member against the board. It also consisted of a user-activated switch coupled to the motor and limit switches to limit the movement of the eraser. Smart White Board Eraser performs the cleaning task automatically by just pressing a button. It cleans efficiently and convenient to use besides saving the precious teaching and learning time and is cost effective.